Toward greener supply chains: is there a role for the new ISO 50001 approach to energy and carbon management? - de Sousa Jabbour, Ana Beatriz Lopes; Verdério Júnior, Sílvio Aparecido [UNESP]; Jabbour, Charbel José Chiappetta; Leal Filho, Walter; Campos, Lucila S.; De Castro, Rosani (Springer Nature, 2017)
Considering the increased interest of stakeholders in climate change and a low-carbon economy, this article has investigated and identified several contributions of the ISO 50001 in support of the adoption of green supply chain management (GSCM). In this context, energy efficiency and reduced CO2 emissions are critical. Therefore, the proposal for and the requirements of ISO 50001 can generate useful insights on how to structure green and low-carbon supply chains, hence helping to address the challenges posed by climate change.
Keywords: Climate change; Green supply chain management (GSCM); International Organization for Standardization (ISO) 50001; Low-carbon supply chain management (LCSCM); Sustainable operations